IMPLEMENTASI RUANG TERBUKA HIJAU PUBLIK MENURUT PERATURAN WALIKOTA PAREPARE NOMOR 64 TAHUN 2020 DI KOTA PAREPARE - Iqrar, Andi Muhammad (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
The growth of the environment in Indonesia is an interesting thing. The problems currently faced by almost every city in Indonesia show the increasingly minimal growth of the public space sector in urban areas. Especially green open spaces, large cities generally have green open spaces with a minimum area of ​​less than 10% as assessed from the area of ​​each city itself. This condition is far below the mandate of Law Number 26 of 2007 concerning Green Open Space in Indonesia, the minimum target for managing public green open spaces is 20% of the area of ​​a city or certain region. Of course, it is a legal commitment that requires local governments and urban authorities to protect and maintain. This study aims to determine the Implementation of the Parepare Mayor Regulation Number 64 of 2020 concerning the Management of Public Green Open Spaces in Parepare City and the inhibiting factors of the Parepare Mayor Regulation Number 64 of 2020 in the management and arrangement of Public Green Open Spaces in Parepare City. The author uses an empirical legal research method, by examining the things that happen behind the implementation of laws and regulations. Through the mandate of the regulations implemented by the Mayor of Pare Pare in the arrangement and management of Green Open Spaces, it is still below the specified standards, due to the dynamics of new policies, lack of integration of related stakeholders and minimal knowledge of the importance of Green Open Spaces.